Structure elucidation and photochemistry of substituted carboxylic compounds by low temperature matrix-isolation and solid state vibrational spectroscopy - Fausto, Rui (1999)
Molecular structures and chemical reactivity (aggregation, phase transitions and photochemistry) of a series of substituted carboxylic acids were studied by low temperature matrix isolation and solid state vibrational spectroscopy, complemented by ab initio molecular orbital calculations. The conformational preferences exhibited by the isolated molecules of the systems under study are analyzed, and the effects of aggregation, temperature change and irradiation are discussed.